2011
DOI: 10.1007/s13300-011-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

A diabetes education multimedia program in the waiting room setting

Abstract: IntroductionThis study evaluated the impact of a waiting room-administered, low-literacy, computer multimedia diabetes education program on patient self-management and provider intensification of therapy.MethodsIn this randomized, controlled trial, 129 participants either viewed a computer multimedia education program (intervention group) or read an educational brochure (control group) while in the waiting room. Participants were uninsured, primarily ethnic minority adults with type 2 diabetes receiving care f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 16 publications
2
76
0
Order By: Relevance
“…Both CD‐ROMs found a significant increase ( P < 0.001) in physical activity; however, one found that as moderate activity increased (33%) lifestyle activity decreased (14.9%). The computer‐learning intervention found a significant small increase (3%, P < 0.05), but a larger increase in the control (26.45%), which the authors attributed to self‐rating of physical activity.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Both CD‐ROMs found a significant increase ( P < 0.001) in physical activity; however, one found that as moderate activity increased (33%) lifestyle activity decreased (14.9%). The computer‐learning intervention found a significant small increase (3%, P < 0.05), but a larger increase in the control (26.45%), which the authors attributed to self‐rating of physical activity.…”
Section: Resultsmentioning
confidence: 97%
“…The number of participants who actively engaged in the intervention exceeded 80% in seven studies: four web‐based , two mobile phone and one CD‐ROM . When decreasing to 70%, five more were deemed to have an acceptable participation rate: three web‐based , one CD‐ROM and the computer learning based . Two web‐based interventions showed a steep decline in use over time .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is congruent with that reported by Khan et al . (), which showed no differences in HbA1c levels between the multimedia and brochure groups 3 months subsequent to the intervention. However, only 25% of the participants in Khan et al .…”
Section: Discussionmentioning
confidence: 85%
“…However, only 25% of the participants in Khan et al . 's () study received insulin therapy, which differed significantly from the participant composition of our study, since all patients were receiving insulin therapy. Therefore, it is not possible to make a meaningful comparison between these two studies.…”
Section: Discussionmentioning
confidence: 97%